PEMANFAATAN PEMBELAJARAN OPEN-ENDED BERBANTUAN GAME EDUKASI UNTUK MENINGKATKAN BERPIKIR KREATIF PESERTA DIDIK PADA MATERI BILANGAN CACAH - ACHMAD FIRDAUS (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
Creative thinking is an important component in preparing for the alpha generation. A study shows that in the future creative work will take on multiple roles, because routine work with repetitive patterns will be taken over by machines and other automated processes. Practicing creative thinking skills can use open-ended learning assisted by educational games. This research is a best practice conducted to train students' mathematical creative thinking abilities. The subjects in this study were 30 grade VI students at SD Al Muslim Bekasi. The research instrument used was an educational game